Facile construction of copper mesh surface from superhydrophilic to superhydrophobic for various oil-water separations - Zhang, Xudong; Pan, Yamin; Zhao, Junyang; Hao, Xiaoqiong; Wang, Yaming; Schubert, Dirk W.; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Engineered Science, 2019)
Specially wettability materials offer a new pathway for effective oil-water separation. However, these materials with desired wettability, simple process and low cost as well as high efficiency separation are still urgently needed. Herein, facile strategies, acid etching and PDMS coating, were reported for the construction of copper mesh surfaces with special wettability from superhydrophilic to superhydrophobic. In the first acid etching, copper mesh surface exhibits a superhydrophilic and underwater superoleophobic properties, and the etched copper mesh with high separation efficiencies (92%) was obtained. After PDMS coating, a low adhesion superoleophilic and superhydrophobic copper mesh shows high water contact angle of 153°, high flux ( 31000 L*m-2*h-1), excellent anti-icing and self-cleaning performances. Additionally, after UVB, mechanical wear, hot water and acid/alkaline solution treating, the coated mesh still showed excellent water-repellency performance. Moreover, the coated mesh by connecting with a vacuum pump was used for continuous oil-water separation. This work provides not only a simple and efficient method to fabricate controllable wettability copper mesh with oil-recovery ability but also a new opportunity for potential applications in continuous oil-water separation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Low adhesion; Oil-water separation; Superhydrophobic; Superoleophilic